Assessment of Justified Distribution Factors Versus Bialek’s Methods for Transmission Usage Evaluation - H. Radzi, N.; H. Ali, M.; N. Abdullah, M.; A. Jumaat, S.; Salimin, S.; Hamdan, R. (International Journal of Engineering and Technology, 2019)
In restructuring electricity market, the electricity business has been separated to three major parts which are generation, transmission and distribution companies. For transmission, the most important component is the transmission line because transmission lines transmitting the power flow from generation to distribution. One of the issues of transmission utility is allocating the charges to the transmission user. The charges must be fair and accurate to all of the transmission users. In addition, an efficient transmission usage evaluation is important to be developed for determining the actual power usage of generators and loads to transmission line. Hence, this paper presents the assessment of Justified Distribution Factors versus Bialek’s methods for determine the efficient transmission usage scheme. The DC power flow method is used in this project as the transmission utilities prefer to choose this simple and easy method in determining the transmission service charges. A case study on 4 bus system was carried out in order to test the developed methodology. Power World Simulator also was used in order to identify the net power flow of each line. In conclusion, this paper focuses on to identify the best method of transmission usage evaluation for transmission service charge methodology.